Pathophysiological hypotheses of the triad in abusive infant shaking : A systematic review and analysis of corroborated cases - Thiblin, Ingemar; Wingren, Carl Johan; Emad, Jacob Andersson; Tamsen, Fredrik (Forensic science international. Synergy, 2025)
Subdural hemorrhage, retinal hemorrhages, and encephalopathy are associated with the medical diagnosis of abusive head trauma. These findings have also been observed in children exposed to admitted or witnessed shaking. There are various suggested mechanisms behind these findings. One mechanism is exclusive to intentional shaking, while the other suggested mechanisms are compatible with both intentional and accidental violence as well as an underlying illness. We performed a systematic literature review of case reports on triad findings with subsequent analysis on the empirical consequences of three mechanistic hypotheses: (1) the outcome components arise independently following acceleration-deceleration forces during shaking; (2) the outcome components are partially dependent and caused by pathophysiological mediators following hypoxia caused by damage to the brainstem or cervical spinal cord by shaking; (3) the outcome factors are partially dependent and are caused by re-bleeding triggered by shaking in chronic subdural hematoma. From a total of 9628 articles, we identified twelve publications including in total 100 cases that met the inclusion criteria. We identified no sufficiently detailed case report, but nine cases had information that allowed for tentative testing of the hypotheses. Three cases had findings consistent with that triad findings are partially dependent and related to chronic subdural re-bleeding (hypothesis 3), whereas no case provided support for the other hypotheses. Thus, published cases do not provide the information needed to understand the mechanism underlying triad findings in infants subjected to shaking.
© 2025 The Authors.